Strategi Komunikasi Badan Pendapatan Daerah Upaya Meningkatkan Kesadaran dan Kepatuhan Wajib Pajak Restoran (Studi kasus pada kantor BAPENDA Lampung Utara) - Suci Ria Ardinata; Hagi Julio Salas (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the communication strategies implemented by the Regional Revenue Agency in increasing awareness and compliance of restaurant taxpayers in North Lampung Regency. This study uses a qualitative descriptive method, with data collection techniques through document studies and field research in the form of interviews. The findings show that the communication strategies used include delivering persuasive messages through direct socialization, utilizing social media, and a service approach that focuses on taxpayers. These strategies aim to increase taxpayer understanding, compliance, and participation in carrying out their obligations. In restaurant tax revenue, there are several aspects of communication that are indicators of taxpayer assessment, namely: 1) Service to taxpayers, 2) Principle of justice, 3) Legal certainty and its enforcement, 4) Transparency in administration, and 5) Restaurant tax collection process. In addition to socialization, the North Lampung Bapenda also carries out counseling and coaching activities for business actors as part of an effort to increase their compliance in paying restaurant taxes.